2010
DOI: 10.1086/656598
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Seroprevalence and Seroconversion among US Military Service Members Deployed to Afghanistan

Abstract: Although subpopulations may be at higher risk for HEV exposure during deployment, the risk among US service members deployed to Afghanistan in this study was low. Previously implemented and current preventive measures in theater appear to have been adequate. With future deployments to new areas or changes in military operations in areas of risk, continued surveillance for HEV infection in the military will be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 42 publications
1
30
1
Order By: Relevance
“…There are other findings in contrast to the low prevalence that Eick et al [1] found in these US troops prior to deployment. A study of the National Health and Nutrition Examination Survey (NHANES) sample of the general US population, in which a similar assay was used, found an antibody seroprevalence of 21% to HEV and a seroprevalence of 8% among subjects under 30 years of age who were born in the United States [12].…”
contrasting
confidence: 63%
See 3 more Smart Citations
“…There are other findings in contrast to the low prevalence that Eick et al [1] found in these US troops prior to deployment. A study of the National Health and Nutrition Examination Survey (NHANES) sample of the general US population, in which a similar assay was used, found an antibody seroprevalence of 21% to HEV and a seroprevalence of 8% among subjects under 30 years of age who were born in the United States [12].…”
contrasting
confidence: 63%
“…The data of Eick et al [1], however, raise several questions that are open to a few interpretations. As the authors discuss, the very low HEV seroprevalence found in subjects prior to their deployment could be related to the serum dilution used in the assay or the cutoff used for seropositivity [10].…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However, for some non-epidemic countries, i.e. the Netherlands (1.1%; [55]), Italy (1.0%; [56]), Switzerland (3.2%; [57]), Spain (2.8%; [58]), USA (1.1%; [59]) and Japan (5.3%; [60]) rather low prevalences were reported.…”
Section: Results Of Commercial Igg Line Immunoassaymentioning
confidence: 99%